Effects of rotation speed and time, as solvent removal parameters, on the physico-chemical properties of prepared α-tocopherol nanoemulsions using solvent-displacement technique - Jafari, Azizeh (Food Sci Biotechnol, 2019)
A bottom-up approach based on solvent-displacement technique was used to prepare α-tocopherol nanoemulsions. Effects of two main evaporation parameters namely, rotation speed (1 × 10–9 × 10 rpm) and rotation time (5–15 min) of utilized vacuum rotary evaporator, on the mean particle size, polydispersity index (PDI) and α-tocopherol degradation of the formed nanodroplets were evaluated using response surface methodology. Obtained results suggested three polynomial regression models for predicting the studied response variables’ affected by selected evaporation parameters. Relatively high coefficients of determination for suggested models (> 0.7839) confirmed the suitability of the generated models. Multiple-optimization procedure revealed that the optimum amounts of evaporation speed and time were 30 rpm and 10 min, respectively, which in that, prepared spherical α-tocopherol nanoemulsions had mean particle size, PDI and concentration values of 48.9 nm, 0.232 and 358.7 mg/L, respectively.